Analysis of the Public Servants' Needs. Case Study: Romania, the North-West Region - Simona Claudia CREȚA; Sorin Dan ŞANDOR (Transylvanian Review of Administrative Sciences, 2011)
Considering that individuals can fulfill some of their needs at the workplace, we may assume that, from the moment people choose a job, they are oriented toward those organizations that ease needs’ satisfaction and quitting that job is less likely when the dominant work needs are met. This paper aims to identify and analyze the needs of public servants from the North-West Region of Romania. The research was conducted in two distinct parts: the identification of needs was made using interviews and the analysis was based on data collected by self-administrated questionnaires. Specific needs of public servants were identified, along with general needs which are expressed by employees from other sectors. 77 needs were analyzed and they were grouped in 22 dimensions following the application of a questionnaire to 343 employees. The results showed that there are three major needs that public servants have namely the need for an optimal organizational climate, the need to have a career and the need to have specific work characteristics.